2005
DOI: 10.1002/cbdv.200590051
|View full text |Cite
|
Sign up to set email alerts
|

Abietane Diterpenoids from the Roots of some MexicanSalvia Species (Labiatae): Chemical Diversity, Phytogeographical Significance, and Cytotoxic Activity

Abstract: From the roots of some Mexican Salvia species, classified in subgenus Jungia, several diterpenoids belonging to abietane (i.e., 3-7), salvifolane (9-->20,10-->6)-diabeoabietane) (i.e., 2), and totarane (i.e., 10) carbocyclic skeletons were isolated together with two 20-nor- and one 6,7-secoabietane derivatives, 1 and 9, and 8, respectively. While compounds 2-10 were previously known from different sources, compound 1 is a new 20-norabietane derivative, whose structure was deduced by spectroscopic means and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…Among these active plant species the genus Salvia has been investigated for cytotoxic activities on cultures of different human tumor cell lines using crude extracts, oily fractions or isolated compounds [24][25][26]. In a recent study Fiore et al demonstrated antiproliferative activity for S. dominica, collected from Jordan, against colorectal adenocarcinoma, choriocarcinoma, prostate adenocarcinoma, B lymphoblast, glioblastoma and endometrium adenocarcinoma cell lines [27].…”
Section: Resultsmentioning
confidence: 99%
“…Among these active plant species the genus Salvia has been investigated for cytotoxic activities on cultures of different human tumor cell lines using crude extracts, oily fractions or isolated compounds [24][25][26]. In a recent study Fiore et al demonstrated antiproliferative activity for S. dominica, collected from Jordan, against colorectal adenocarcinoma, choriocarcinoma, prostate adenocarcinoma, B lymphoblast, glioblastoma and endometrium adenocarcinoma cell lines [27].…”
Section: Resultsmentioning
confidence: 99%
“…Labdane, pimarane, kaurane, totarane, clerodane, and abietane diterpenoids have been described for the genus [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In addition, several rearranged pimarane, abietane, and clerodane diterpenoids have been isolated from Salvia species [ 9 , 10 , 11 ]. Interesting biological activities such as cytotoxic, antiprotozoal, antioxidant, anti-inflammatory, insect anti-feeding, and psychotropic activities have also been documented for some of the diterpenoids isolated from these plants [ 2 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on several populations of Salvia ballotiflora indicated that this species produced an interesting array of icetexane and abietane diterpenoids. Several members of this type of diterpenoids have been targeted for synthetic work due to their structural features and the biological activity exhibited by some icetexanes [ 16 , 17 , 18 , 19 , 20 ] as anti-proliferative activity, in vitro, against some human cancer cell lines [ 9 , 11 , 21 ]. On this issue, while the aqueous-methanolic extract of S. ballotiflora displayed cytotoxicity to Vero cells [ 22 ], the icetexane derivatives isolated from the chloroform extract of the same species showed cytotoxic activity, with 19-deoxyicetexone [ 23 ] being the most active compound against the HeLa cervical cancer cell line [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper regarding the synthesis of several icetexane diterpenoids this fact has been addressed [51]. Salviasperanol (65), is an icetexane diterpenoid originally isolated from the roots of Salvia aspera M. Cariocal (66) is a 6,7-seco-abietane derivative isolated originally from Coleus barbatus [52] and recently from the roots of S. aspera and S. anastomosans [14]. Compound (66) constitutes the first example of such a rearranged abietane derivative isolated from a Salvia species belonging to Jungia Subgenus.…”
Section: 10mentioning
confidence: 99%